AKUNTABILITAS PENYELENGGARAAN PENDIDIKAN DALAM PERSPEKTIF ISLAM - Khalis, Nur (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2018)
This research describes that Islamic education systemconstitute organizing effort processes activity toeducation that has based Islam teaching with passthrough systemic approaching so deep its operationalperform consisting of part system of elementary,intermediate and college who shall have levelsinscholarly quality and technology. Based on histories,itcomes into the world formal education institutes inshaped school or madrasah in Islam to constitute isdevelopment of teaching and education systemhappened since Nabi Saw has gootten at mosque -kuttab, halaqah, suffah-, until became formal institute asschool, madrasah, ma’had danuniversity. New paradigmin education shall can revamp learning paradigm ofteacher oriented to student oriented,direct learning ascolaborative learning to team wor, learning to know toskill,learning that gets to orient to content to learningthat accentuates to process, learning based curriculumto gets life skill, learning gets individual's character tolearning that gets group character, of learning that getscenter at spatial class to learning that gets to society.